Genetic diversity and species delimitation in Rhamdia (Siluriformes: Heptapteridae) in South America, with a redescription of R. quelen (Quoy & Gaimard, 1824) - Angrizani, Rafael Costa; Malabarba, Luiz Roberto (Zootaxa, 2020)
More than 100 species have been referred to Rhamdia since its description, but in the last revision of the genus more than two decades ago, only eleven species have been considered as valid. Rhamdia quelen was then redefined to include 47 junior synonyms, resulting in a species with a large distribution in the Neotropics, from Mexico to Argentina. Populations of Rhamdia from west of the Andes have been recently removed from the synonymy of R. quelen, and currently there are 27 species recognized in the genus. Most cis-Andean populations, however, remain referred to the R. quelen species complex. In this paper, we use species delimitation methods and multilocus phylogenetic analyses to delimit the species contained in the R. quelen species complex in cis-Andean river drainages. Eighteen MOTUs in the gene tree were recovered with high support. We further demonstrate that the previous designation of a neotype for R. quelen is invalid, and has to be replaced by the proper designation of a neotype from the type locality of the species. The neotype is designated herein and R. quelen is diagnosed and redescribed.